Soft magnetic alloy powder, powder magnetic core, and coil component

CN115705944BActive Publication Date: 2026-10-27TDK CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210920860.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-06-27
Filing Date
2022-08-02
Publication Date
2026-10-27
Estimated Expiration
2042-08-02

AI Technical Summary

Benefits of technology

[0008]发明所要解决的技术问题

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115705944B_ABST
    Figure CN115705944B_ABST
Patent Text Reader

Abstract

Provided is a soft magnetic alloy powder having good saturation magnetization and coercive force, and capable of providing a powder magnetic core containing the soft magnetic alloy powder with good permeability and DC superposition characteristics while reducing core loss. The present invention is a soft magnetic alloy powder containing soft magnetic alloy particles. The soft magnetic alloy particles contain Fe and Si. The soft magnetic alloy particles are composed of a plurality of crystallites and grain boundaries between the plurality of crystallites. There are sites of Si segregation in the crystallites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to soft magnetic alloy powder, pressed magnetic core, and coil components. Background Technology

[0002] Patent Document 1 discloses an invention of a metallic magnetic material containing soft magnetic alloy particles composed of Fe and Si. This metallic magnetic material includes a layer containing a high concentration of Si between the soft magnetic alloy particles.

[0003] Patent document 2 describes an invention containing soft magnetic alloy particles of Fe and Ni. These soft magnetic alloy particles consist of multiple microcrystals and grain boundaries between the microcrystals, with a high-resistivity layer present at these grain boundaries.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: Japanese Patent Application Publication No. 2016-143700

[0007] Patent Document 2: Japanese Patent Application Publication No. 2018-206835 Summary of the Invention

[0008] The technical problem that the invention aims to solve

[0009] The purpose of this invention is to provide a soft magnetic alloy powder that has good saturation magnetization and coercivity, and to enable the pressed magnetic core containing the soft magnetic alloy powder to have good permeability and DC superposition characteristics, while reducing core loss.

[0010] Technical solutions for solving technical problems

[0011] To achieve the above objectives, the present invention provides a soft magnetic alloy powder, characterized in that the soft magnetic alloy powder contains soft magnetic alloy particles.

[0012] The soft magnetic alloy particles contain Fe and Si.

[0013] The soft magnetic alloy particles are composed of multiple microcrystals and grain boundaries between the multiple microcrystals.

[0014] There are sites of Si segregation in the microcrystals.

[0015] The soft magnetic alloy powder of the present invention, by possessing the above-described characteristics, can achieve good saturation magnetization and coercivity. Furthermore, it can produce powder-pressed magnetic cores containing this soft magnetic alloy powder with good permeability and DC superposition characteristics, while simultaneously reducing core losses.

[0016] The soft magnetic alloy particles may also contain only Fe, Si, and unavoidable impurities.

[0017] The Si content in the soft magnetic alloy particles can also be above 3.0% by mass and below 11.0% by mass.

[0018] The pressed powder magnetic core of the present invention contains the above-mentioned soft magnetic alloy powder.

[0019] The coil component of the present invention contains the above-described pressed powder magnetic core. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the soft magnetic alloy particles of this embodiment.

[0021] Figure 2 This is a COMPO image of the soft magnetic alloy particles in sample No. 3.

[0022] Figure 3 This is a Si mapping image of the soft magnetic alloy particles in sample No. 3.

[0023] Figure 4 It is Figure 3 Binarized image.

[0024] Figure 5 This is a COMPO image of the soft magnetic alloy particles in sample No. 6.

[0025] Figure 6 This is a Si mapping image of the soft magnetic alloy particles in sample No. 6.

[0026] Figure 7 It is Figure 6 Binarized image.

[0027] Figure 8 This is a COMPO image of the soft magnetic alloy particles in sample No. 7.

[0028] Figure 9 This is a Si mapping image of the soft magnetic alloy particles in sample No. 7.

[0029] Figure 10 It is Figure 9 Binarized image.

[0030] Explanation of reference numerals in the attached figures

[0031] 2… Soft magnetic alloy particles

[0032] 2a…(soft magnetic alloy) particle surface

[0033] 4…microcrystals

[0034] 4a…grain boundary Detailed Implementation

[0035] Hereinafter, preferred embodiments of the present invention will be described with reference to the accompanying drawings, but the embodiments of the present invention are not limited to the embodiments described below.

[0036] The soft magnetic alloy powder of this embodiment contains soft magnetic alloy particles 2. The soft magnetic alloy particles 2 are as follows: Figure 1 The diagram shows a structure consisting of multiple microcrystals 4 and grain boundaries 4a existing between the microcrystals 4.

[0037] The soft magnetic alloy particles 2 contained in the soft magnetic alloy powder of this embodiment are characterized by the presence of Si segregation sites within the microcrystals 4. Hereinafter, the Si segregation sites will sometimes be simply referred to as Si segregation portions.

[0038] It is assumed that the Si segregation portion is the part of the microcrystal 4 with a higher resistance than the portion outside the Si segregation portion. Since the Si segregation portion is contained in the microcrystal 4, the resistance in the microcrystal 4 becomes higher. By increasing the resistance in the microcrystal 4, the generation of eddy currents in the microcrystal 4 is suppressed. As a result, the pressed powder magnetic core made using soft magnetic alloy powder containing soft magnetic alloy particles 2 with Si segregation portions in the microcrystal 4 exhibits good permeability, especially at high frequencies, and the core loss is reduced. In particular, when the crystal grain size of the microcrystal 4 is large, the effect of suppressing the generation of eddy currents caused by the presence of Si segregation portions in the microcrystal 4 becomes greater.

[0039] Alternatively, Si segregation may exist within the grain boundary 4a. It is believed that the presence of Si segregation within the grain boundary 4a increases its resistivity. This increased resistivity suppresses the generation of eddy currents in the soft magnetic alloy particles 2.

[0040] It is particularly preferred that Si segregation exists in both the microcrystals 4 and the grain boundaries 4a. The pressed powder magnetic core made using soft magnetic alloy powder containing soft magnetic alloy particles 2 with Si segregation in both the microcrystals 4 and the grain boundaries 4a exhibits good permeability at high frequencies and reduced core loss.

[0041] There is no particular limitation on the average particle size of the soft magnetic alloy particles 2, for example, it can be 1 μm or more and 50 μm or less. In addition, there is no particular limitation on the average crystallite diameter of the microcrystals 4, for example, it can be 0.5 μm or more and 20 μm or less.

[0042] The soft magnetic alloy particles 2 contain at least Fe and Si. Other elements may also be included within a range that does not significantly affect the properties of the soft magnetic alloy powder containing the soft magnetic alloy particles 2. For example, each of the other elements may contain 5.0% by mass or less, or 1.0% by mass or less. Furthermore, the total content of the other elements may be 10.0% by mass or less, or 2.0% by mass or less.

[0043] However, when the soft magnetic alloy particles 2 contain Ni, it is difficult for the microcrystals 4 to contain Si segregation. Furthermore, raw materials containing Ni are expensive. Therefore, the Ni content is preferably 5.0% by mass or less, and more preferably 0.5% by mass or less.

[0044] The soft magnetic alloy particles 2 may also contain only Fe, Si, and unavoidable impurities. In this case, the content of unavoidable impurities may be less than 2.0% by mass or less than 1.0% by mass.

[0045] The Si content in the soft magnetic alloy particles 2 is not particularly limited. It can be 2.0% by mass or more and 12.0% by mass or less, or 3.0% by mass or more and 11.0% by mass or less. With a Si content of 2.0% by mass or more or 3.0% by mass or more, the coercivity of the soft magnetic alloy powder containing the soft magnetic alloy particles 2 is easily reduced. Furthermore, the core loss of the pressed powder core containing this soft magnetic alloy powder is easily reduced. With a Si content of 12.0% by mass or less or 11.0% by mass or less, the saturation magnetization of the soft magnetic alloy powder containing the soft magnetic alloy particles 2 is easily increased. Additionally, the permeability and DC superposition characteristics of the pressed powder core containing this soft magnetic alloy powder are easily improved.

[0046] It can be confirmed by observing the backscattered electron image (COMPO image) formed by EPMA that the soft magnetic alloy particles 2 are composed of multiple microcrystals 4 and grain boundaries 4a existing between the microcrystals 4. Figure 2 The image shown is a COMPO image of the soft magnetic alloy particles of this embodiment. The magnification of the COMPO image is not particularly limited, as long as it is a magnification and resolution sufficient to confirm the aforementioned microstructure of the soft magnetic alloy particles. For example, a magnification of 500x or more and 5000x or less is acceptable.

[0047] Furthermore, Si segregation zones were confirmed in grain boundary 4a and microcrystal 4 by using EPMA for Si mapping. Figure 3 The middle shows Figure 2 The image shows a Si mapping of the soft magnetic alloy particles. In this embodiment, the portion where the Si concentration is 105% or more relative to the average Si concentration of the soft magnetic alloy particles is defined as a Si segregation zone. The size of a single Si segregation zone is set to 0.4 μm. 2 That's all. Size less than 0.4μm 2 The portion is not considered as a Si segregation region.

[0048] Will Figure 3 The Si mapping image shown is a binarized image of the portion where the Si concentration is above 105% relative to the average Si concentration of the soft magnetic alloy particles and the portion where the Si concentration is below 105%. Figure 4 By comparison Figure 2 and Figure 4 This allows us to confirm the presence of Si segregation zones within grain boundaries and within microcrystals. For example... Figure 3 , Figure 4 As shown, Si segregation exists in the grain boundaries, and the Si segregation exists in the microcrystals in a mesh-like manner.

[0049] Figures 2-4 This indicates soft magnetic alloy particles with a Si content of 4.5% by mass. Figures 2-4 The soft magnetic alloy particles shown are those of sample No. 3, described later. Additionally, in Figures 5-7 , Figures 8-10 The image also shows the COMPO image, the Si mapping image, and the binarized Si mapping image of the soft magnetic alloy particles. Figures 5-7 The soft magnetic alloy particles shown are those of sample No. 6 (with a Si content of 6.5% by mass) described later. Figures 8-10 The soft magnetic alloy particles shown are those of sample No. 7 (with a Si content of 8.0% by mass), described later.

[0050] There is no particular limitation on the proportion of Si segregation in the grain boundary 4a. On the cross-section of the soft magnetic alloy particle 2, the total area of ​​Si segregation in the grain boundary 4a is preferably 70% or more relative to the total area of ​​the grain boundary 4a.

[0051] There is no particular limitation on the proportion of Si segregation in microcrystal 4. On the cross-section of the soft magnetic alloy particle 2, the total area of ​​Si segregation in microcrystal 4 is preferably 5% or more relative to the total area of ​​microcrystal 4.

[0052] Furthermore, an oxide coating can also exist on the particle surface 2a of the soft magnetic alloy particles 2. For example, the thickness of the oxide coating can be less than 5.0 nm or less than 3.0 nm. The thinner the oxide coating, the easier it is to reduce the hardness of the soft magnetic alloy particles 2 and the easier it is to improve their machinability. By improving the machinability of the soft magnetic alloy particles 2, it is easier to increase the density of the powder core containing the soft magnetic alloy particles 2.

[0053] The soft magnetic alloy powder of this embodiment contains the soft magnetic alloy particles 2 of this embodiment. The soft magnetic alloy powder of this embodiment need not consist solely of the soft magnetic alloy particles 2 of this embodiment; it may also contain soft magnetic alloy particles that do not contain Si segregation in the microcrystals. The proportion of soft magnetic alloy particles containing Si segregation in the microcrystals of the soft magnetic alloy powder of this embodiment is preferably 50% or more based on the particle number. Furthermore, the proportion of soft magnetic alloy particles containing Si segregation on both the grain boundaries and microcrystals of the soft magnetic alloy powder of this embodiment is preferably 50% or more based on the particle number.

[0054] Hereinafter, an example of a method for manufacturing soft magnetic alloy powder composed of soft magnetic alloy particles according to this embodiment will be described, but the method for manufacturing soft magnetic alloy powder according to this embodiment is not limited to the method described below. Furthermore, in this embodiment, an aggregate of substances containing multiple particles is used as powder.

[0055] First, prepare the raw materials for the soft magnetic alloy powder. The raw materials can be monomers such as metals, or alloys. There are no particular restrictions on the form of the raw materials. Examples include ingots, chunks, or shots.

[0056] Next, the prepared raw materials are weighed and mixed. At this point, the weighing is performed in a manner that yields a soft magnetic alloy powder with the desired final composition. Furthermore, the mixed raw materials are melted and combined to obtain a molten liquid. There are no particular limitations on the apparatus used for melting and mixing. Examples include furnaces.

[0057] Furthermore, soft magnetic alloy powder can be produced from molten metal. There are no particular limitations on the method for producing soft magnetic alloy powder from molten metal; methods such as gas atomization, rotary table atomization, and water atomization can be used. In the gas atomization method, molten metal is continuously supplied as a fluid using a nozzle or similar means, and high-pressure gas is used to collide with the supplied molten metal, causing rapid cooling. This process allows the production of soft magnetic alloy powder.

[0058] Next, the obtained soft magnetic alloy powder is heat-treated. At this time, by performing heat treatment under appropriate heat treatment conditions, it is possible to make the grain boundaries and microcrystals contain Si segregation.

[0059] Preferred heat treatment conditions vary depending on the composition of the soft magnetic alloy powder intended for use, but generally the holding temperature during heat treatment is set to 800°C or higher and 1100°C or lower, preferably 800°C or higher and 900°C or lower. The holding time is set to 10 minutes or higher and 3 hours or lower, preferably 10 minutes or higher and 2 hours or lower.

[0060] Furthermore, the cooling rate up to 300°C after heat treatment is set to be 0.1°C / s or higher and 100°C / s or lower. There are no particular restrictions on the heat treatment atmosphere, but it is usually set to an inert gas atmosphere such as nitrogen or argon, or a vacuum.

[0061] In particular, by setting the holding temperature during heat treatment to a high temperature as described above, and then setting the cooling rate to a fast rate as described above, it is possible to include Si segregation portions not only at grain boundaries but also at crystallites. When the cooling rate is too slow, Si segregation portions are easily formed at grain boundaries, but not easily at crystallites. When the cooling rate is too fast, Si segregation portions are not easily formed at either grain boundaries or crystallites. That is, when the cooling rate is too fast, Si is easily and uniformly contained within the soft magnetic alloy particles.

[0062] When the temperature is kept too high, the crystallites tend to become coarse. When the temperature is kept too low, the grain boundaries are more likely to contain Si segregation, but the crystallites are less likely to contain Si segregation.

[0063] The soft magnetic alloy powder composed of soft magnetic alloy particles as described above can be obtained in this embodiment. Furthermore, a pressed powder core can be obtained using a method typically used for the soft magnetic alloy powder in this embodiment. There are no particular limitations on the method for obtaining the pressed powder core.

[0064] Alternatively, a soft magnetic alloy powder obtained by mixing the soft magnetic alloy powder of this embodiment with other soft magnetic metal powders can be used to obtain the pressed powder core. There are no particular limitations on the types of other soft magnetic metal powders. Examples include soft magnetic metal powders with an average particle size smaller than that of the soft magnetic alloy powder of this embodiment. The average particle size of the aforementioned soft magnetic metal powder with a small average particle size can also be 0.5 μm or more and 5 μm or less. There are no particular limitations on the material of the aforementioned soft magnetic metal powder with a small average particle size. Examples include metals such as pure iron, or alloys such as permalloy.

[0065] When mixing the soft magnetic alloy powder of this embodiment with the soft magnetic metal powder with the small average particle size described above, there is no particular limitation on the proportion of the soft magnetic alloy powder of this embodiment. For example, it can be 50% by mass or more.

[0066] Coil components, such as inductors, reactors, and motors, can be obtained using the powder core method commonly used in this embodiment. In particular, coil components with high saturation current, low coil resistance, high frequency, and low loss can be obtained. Furthermore, when using the powder core of this embodiment, the coil components can be easily miniaturized. There are no particular limitations on the method for obtaining the coil components.

[0067] Example

[0068] The present invention will be described in more detail below with examples and comparative examples, but the present invention is not limited to the following examples.

[0069] [Preparation of soft magnetic alloy powder]

[0070] First, ingots, blocks, or pellets of Fe and Si monomers are prepared. Next, the Fe and Si monomers are mixed to achieve the Si content shown in Tables 1 and 2, and contained in a furnace configured within a gas atomization device. Then, in an inert atmosphere, a working coil located outside the furnace is used to heat the furnace to above 1500°C via high-frequency induction, melting and mixing the ingots, blocks, or pellets in the furnace to obtain a molten liquid.

[0071] Next, molten metal is supplied to the furnace through a nozzle located in the furnace, while a gas pressure of 1–10 MPa is used to rapidly cool the supplied molten metal by impact, thereby producing Fe-Si based soft magnetic alloy powders with the Si content shown in Tables 1 and 2. Furthermore, in all the soft magnetic alloy powders, the average particle size of the soft magnetic alloy particles is set to 25 μm.

[0072] Furthermore, the obtained soft magnetic alloy powder was subjected to heat treatment. Table 1 shows the heat treatment conditions for each experimental example recorded in Table 1. In addition, the heat treatment conditions for each experimental example recorded in Table 2 were appropriately controlled within the following ranges: holding temperature: 800°C or higher and 1100°C or lower; holding time: 10 minutes or higher and 3 hours or lower; cooling rate up to 300°C after heat treatment: 0.1°C / s or higher and 100°C / s or lower.

[0073] [Fabrication of Powder-Powdered Magnetic Cores]

[0074] Epoxy resin, used as a binder, is added to heat-treated soft magnetic alloy powder to produce granulated powder. Furthermore, the type and amount of epoxy resin added are appropriately determined based on the composition of each soft magnetic alloy powder. Using this granulated powder, rings with an outer diameter of 18 mm × an inner diameter of 10 mm × a height of 5 mm are formed at a molding pressure of 6 ton / cm². 2 Next, the molded body is held at 180°C for 3 hours in an atmospheric atmosphere to allow the resin to cure, thereby obtaining a ring-shaped pressed powder magnetic core.

[0075] [Evaluation of Soft Magnetic Alloy Powder]

[0076] (Evaluation of magnetic properties)

[0077] The specific saturation magnetization σs and coercivity Hc of the soft magnetic alloy powders in each experimental example were determined. σs was measured using a vibrating sample magnetometer (VSM) under a magnetic field of 1000 kA / m. Hc was measured using an Hc meter. The results are shown in Tables 1 and 2. Furthermore, σs above 120 emu / g is considered good, and above 140 emu / g is considered even better. Hc below 1000 A / m is considered good, and below 800 A / m is considered even better.

[0078] (Observation of Si segregation)

[0079] The cross-section of a composite obtained by resin mixing of soft magnetic alloy powder was observed and ground to specifically identify the presence of Si segregation within grain boundaries and crystallites. Specifically, the location of grain boundaries and crystallites within the soft magnetic alloy particles was identified using a COMPO image obtained by observing the composite at 2000x magnification using an EPMA (JEOL JXA-8500F). Furthermore, the presence of Si segregation within grain boundaries and crystallites within the soft magnetic alloy particles was identified using a Si mapping image obtained by observing the composite at 2000x magnification using an EPMA (JEOL JXA-8500F).

[0080] The EPMA measurement conditions were: accelerating voltage 15.0 kV and irradiation current 1.030 × 10⁻⁶ kV. -7 A. Irradiation time: 40.00 ms; Number of measurement points: 200 × 200; Measurement point interval: 0.20 μm. Furthermore, regarding the Si content, the total content of the four elements Si, P, O, and Fe is calculated as 100% by mass. P and O are unavoidable impurities. Additionally, the composition of the portion outside the soft magnetic alloy particles is inaccurate. This is because the portion outside the soft magnetic alloy particles contains a large amount of carbon (C) derived from the compounded resin.

[0081] In this embodiment, at least 10 soft magnetic alloy particles were observed on a cross-section obtained by cross-sectional grinding of the composite obtained by resin mixing of soft magnetic alloy particles. Furthermore, in each embodiment, the proportion of soft magnetic alloy particles with Si segregation in grain boundaries and microcrystals was 70% or more, based on the number of particles. In contrast, in comparative example No. 1, no Si segregation was found in either grain boundaries or microcrystals. Additionally, in comparative example No. 2, the proportion of soft magnetic alloy particles with Si segregation in grain boundaries was 70% or more, but no soft magnetic alloy particles with Si segregation in microcrystals were found. The results are shown in Tables 1 and 2.

[0082] [Evaluation of Powdered Magnetic Cores]

[0083] (Determination of magnetic permeability and DC superposition characteristics)

[0084] The relative permeability μ′ of the pressed powder cores of each embodiment and comparative example was measured at a frequency of 1 MHz. An RF impedance material analyzer (Agilent Technologies 4991A) was used to measure the relative permeability μ′. Furthermore, the relative permeability μ′ when no DC current is applied (i.e., no DC current is superimposed) was defined as μ0, and the relative permeability μ′ when a DC current is superimposed and a DC magnetic field of 20 kA / m is applied was defined as μ0. 20k Calculate μ 20k / μ0 is used to evaluate the DC superposition characteristics. In this embodiment, for μ0, values ​​of 22.0 and above are considered good, and values ​​of 23.0 and above are considered even better. Additionally, for μ... 20k For μ0, values ​​above 0.55 are considered good, and values ​​above 0.60 are considered even better. The results are shown in Tables 1 and 2.

[0085] (Determination of core loss (electrical loss) Pcv)

[0086] For the powder-coated magnetic cores of each embodiment and comparative example, the primary winding was wound 30 times and the secondary winding was wound 10 times. Furthermore, Pcv was measured at a measurement frequency of 0.3 MHz and a magnetic flux density of 25 mT. Additionally, Pcv was measured at a measurement frequency of 3 MHz and a magnetic flux density of 10 mT. Pcv was measured using a BH analyzer (SY-8218 manufactured by Iwasaki Telecommunications Co., Ltd.). Regarding the Pcv measured at a measurement frequency of 0.3 MHz and a magnetic flux density of 25 mT, 600 kW / m... 3 The following settings are considered good, with a power consumption of 500 kW / m³. 3 The following settings are even better. Regarding the Pcv measured at a frequency of 3MHz and a magnetic flux density of 10mT, 2200kW / m 3 The following is set to good, with a power of 2000 kW / m 3 The following settings are considered better. The results are shown in Tables 1 and 2.

[0087]

[0088] Table 2

[0089]

[0090] According to Tables 1 and 2, the embodiments containing Si segregation in the microcrystals of the soft magnetic alloy particles exhibit good magnetic properties. Furthermore, when the powder core is made from the soft magnetic alloy particles, it demonstrates good relative permeability and DC superposition characteristics, with low core loss at any frequency.

[0091] Furthermore, when the Si content is 3.0% by mass or higher, the coercivity of the soft magnetic alloy powder and the core loss of the pressed powder core are reduced, in particular. Additionally, when the Si content is 11.0% by mass or lower, the specific saturation magnetization of the soft magnetic alloy powder and the relative permeability μ′ of the pressed powder core are improved, in particular. Moreover, the DC superposition characteristics of the pressed powder core are excellent.

[0092] In contrast, when the microcrystals of the soft magnetic alloy particles do not contain Si segregation (samples No. 1 and 2), the core loss at high frequencies deteriorates when the powder core is made from the soft magnetic alloy particles.

Claims

1. A soft magnetic alloy powder, wherein, The soft magnetic alloy powder contains soft magnetic alloy particles. The soft magnetic alloy particles contain only Fe, Si, and unavoidable impurities. The Si content in the soft magnetic alloy particles is above 3.0% by mass and below 11.0% by mass. The average particle size of the soft magnetic alloy particles is between 1 μm and 50 μm. The soft magnetic alloy particles are composed of multiple microcrystals and grain boundaries between the multiple microcrystals. The average crystallite diameter is between 0.5 μm and 20 μm. In the microcrystals, there are sites of Si segregation. The Si segregation is defined as the portion where the Si concentration is 105% or higher relative to the average Si concentration of the soft magnetic alloy particles. The size of one of the Si segregation sites is 0.4 μm. 2 above, On the cross-section of the soft magnetic alloy particles, the total area of ​​the Si segregated portions in the microcrystals is more than 5% of the total area of ​​the microcrystals.

2. A pressed powder magnetic core, wherein, The pressed powder core contains the soft magnetic alloy powder as described in claim 1.

3. A coil component, wherein, The coil component contains the pressed powder magnetic core as described in claim 2.

Citation Information

Patent Citations

  • Metal magnetic material and electronic component

    JP2016143700A

  • Soft magnetic alloy particle and electronic component

    JP2018206835A

  • Soft magnetic body composition, manufacturing method thereof, magnetic core, and coil-type electronic component

    CN103943296A